ENGLISH TEACHING METHOD APPLIED BY TEACHERS IN MTs NEGERI MODEL LIMBOTO - Nurwahida Pido; Erliana Dewi (LP2M IAIN Sultan Amai Gorontalo, 2019)
The objectives of this research are: (1) to identify the methods that implemented in teaching English process at 7th grade of MTs Negeri 1 Kabupaten Gorontalo, (2) to know the procedures of English teaching method that implemented in English teaching process of 7th grade of MTs Negeri 1 Kabupaten Gorontalo. The research used qualitative descriptive method, to describe the method that implemented by the teacher in English teaching process.The subjects of this research were English teacher and the students of 7th grade. Instrument used in this research were observation, interview, and documentation. The technique of analyzing data was identifying by reducing, displaying, and drawing conclusion of the data. The results of this research shown that there are four types of language teaching method that used by the English teacher. Those are Discovery Learning, Total Physical Response, Communicative Language Teaching (Role Play), and Direct Method. The teacher implemented the language teaching methods by modifying the procedures of language teaching method.